Impacts of Seastate‐Dependent Sea Spray Heat Fluxes on Tropical Cyclone Structure and Intensity in Fully Coupled Atmosphere‐Wave‐Ocean Model Simulations - B. W. Barr; S. S. Chen (Journal of Advances in Modeling Earth Systems, 2025)
Abstract Air‐sea sensible and latent heat fluxes are fundamental to tropical cyclone (TC) energetics, yet the impacts of seastate‐dependent sea spray heat fluxes on TC structure and intensity remain poorly understood. To explore these impacts, we implement a recently developed parameterization of seastate‐dependent spray heat fluxes into a fully coupled atmosphere‐wave‐ocean model, the Unified Wave INterface–Coupled Model (UWIN‐CM). We conduct UWIN‐CM experiments, both with and without spray, for four TCs covering a broad spectrum of intensities and structural characteristics. Overall, we find that spray evaporation hinders intensification of weak TCs, while direct heating from warm spray droplets promotes intensification of major hurricanes. The effects of spray on open ocean TCs can be summarized in three stages: (1) In tropical storms and weak hurricanes (≤Category 1), spray evaporation cools the boundary layer (BL) throughout the storm, hindering intensification. (2) In stronger TCs, increasing spray production leads to stronger direct heating that warms the eyewall BL, partly offsetting the storm‐scale BL cooling. However, storms remain relatively weaker due to structural inefficiency of cooler BL inflow. (3) With further intensification and even stronger spray production, BL warming eventually overcomes the structural inefficiency and promotes intensification, particularly in major hurricanes (>Category 3), including rapid intensification. The shift in spray heat flux characteristics is initiated by a significant increase in spray production linked to seastate conditions occurring at 10‐m windspeed ≈30 m s−1. Additionally, our results indicate that enhanced spray generation from breaking waves in the coastal zone may strengthen landfalling TCs.